FINGERPRINT ATTENDANCE AND MOTIVATION EFFECT ON WORK DISCIPLINE OF ISLAMIC HIGH SCHOOL TEACHERS IN DEPOK - Novianty, Henny; Akhirson, Armaini (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
The purpose of the study was to determine the effect of the fingerprint attendance system and motivation on the work discipline of teachers at the Dian Didaktika Islamic High School in Depok City-Indonesia. Independent variables are Fingerprint Attendance (X1) and Motivation (X2), and the dependent variable is the teacher’s Work Discipline (Y). This research method was carried out quantitatively with a sample of 30 active teachers in the Science and Social Sciences field. Data are taken through questionnaires. Test the quality of the instrument with a validity test and a reliability test. Classical assumption tests include normality, heteroscedasticity, multicollinearity, multiple linear regression, and R-squared tests. Test the hypothesis with a t-test and F-test. The results showed that fingerprint attendance had a positive and significant impact of 93.7%, motivation had a positive and significant impact of 93.3%, and simultaneously had a positive and significant impact of 96.2%.